Correlation of Kidney Volume on CT-Scan with Kidney Function Tests in Patients with Normal Kidneys at Haji Adam Malik Hospital Medan in 2020-2021 - Harry, M. Randy; Daulay, Elvita Rahmi; Tarigan, Radar Radius (CoinReads Media Prima, 2023)
Introduction: Kidneys have filtration and excretion functions; the glomerular filtration rate (GFR) is considered the best indicator of kidney function and may indicate abnormalities. Kidney volume can be an early indicator of kidney disorders before there is a decrease in kidney function. Changes in kidney volume may indicate structural and functional changes that indicate a disorder or disease progression. Radiological examination such as a CT-Scan has an important role in measuring the size and kidney volume and assessing kidney morphological changes for the diagnosis and staging of kidney disease as well as planning therapy. Objective: This study aims to find a correlation between the estimated kidney volume with the ellipsoid method through CT scanning and estimated kidney function by glomerular filtration rate in patients with normal kidneys. Method: An analytical study used a case-series design; all subjects were patients who had normal CT-Scan results and normal kidney function at the Haji Adam Malik Hospital in Medan in 2020–2021. Used the consecutive sampling technique and had 90 total samples. Results: There is a moderately positive correlation (r = 0,410-0,499) between volume and kidney function. A moderately negative correlation (r = -0,196 to -0,282) between kidney volume and age. A moderately positive correlation (r = 0,456-0,548) between kidney volume and body weight. There is a moderately negative correlation (r = -0.495) between renal function and age. A moderately positive correlation (r = 0,567) between renal function and body weight. Conclusion: there is a correlation between kidney volume and kidney function, the correlation between kidney volume and body weight, the correlation between kidney function and body weight.